Predicting the Price Direction of Bitcoin Using Twitter Data and Machine Learning - Kanji, Abdul Mannan; Chaudhary, Ishita; Shankar, Rithika Lakshmi; Srinivasa, Gowri (2022 IEEE 2nd International Conference on Data Science and Computer Application (ICDSCA), 2022)
Bitcoin is a decentralized digital currency that was intro- duced in 2009 and since then, has become increasingly popular as one of the most known and highly valued currencies. Contributing factors to its rise include crypto Twitter influencers. An engaged audience on Twitter seems to have an influence on the cryptocurrency market. In this paper, we analyze the impact that tweets have on the price of Bitcoin. Using word-clouds and candlestick plots, we gain insight into the factors that affect Bitcoin prices. We also use various machine learning techniques to automatically classify the sentiment in Tweets related to cryptocurrencies. We incorporate these and other relevant features to build and compare the performance of multiple machine learning models to predict the direction (increase or decrease) of the price of Bitcoin.